A study on students' satisfaction over academic services provided by Paya Besar community college / Nur Fariza Mohd Rahim - Mohd Rahim, Nur Fariza (2013)
Students of any private or public higher learning institutions can be regarded as customers to these organizations. Thus, it is very important to take care of their satisfaction in ensuring the best service and a quality education are delivered to them. Student satisfaction can improve the image of that education institution as well as attracting more students to enroll at that education institution. Community College is one of the public higher learning institutions which responsible in providing good education to youth in helping them developing a better life in the future. This study was carried out in Community College in Pahang which only offering certificate courses for their students. The Community College involved in this study is Paya Besar Community College. Other than that, this study was focused on students ' satisfaction over academic services quality provided by the Community College. The students' satisfaction was measured based on SERVQUAL five dimensions developed by Parasuraman et al. The five dimensions are tangible, reliability, responsiveness, assurance, and empathy. The sampling technique used in getting the sample size is proportionate stratified random sampling. Findings of this study founds that the most influential factors that contribute to the students ' satisfaction over academic services are empathy quality which caring, individualize attention the firm provides to its customers. The group of gender show the higher level of student satisfaction are male student and the program that show the higher level of student satisfaction are National Modular Certificate in Computer Networking.